Consumer Behavior Shifts in Digital Age: Impact on Brand Loyalty - Haris, Abdul (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study investigates how digital advancements reshape consumer behavior and influence brand loyalty. It explores the role of e-commerce, social media, and big data analytics in transforming decision-making, focusing on personalization, ethical considerations, and emotional engagement in brand loyalty. Research Design and Methodology: This study synthesizes insights from various academic sources using a qualitative systematic literature review to identify key trends, challenges, and opportunities in consumer behavior and brand loyalty. Agency theory frames the analysis of evolving consumer-brand interactions in a technology-driven landscape. Findings and Discussion: Consumer behavior has shifted from traditional linear patterns to dynamic, multidimensional decision-making influenced by digital tools. Personalization significantly enhances brand loyalty but raises ethical concerns regarding data use. Social media fosters emotional engagement while increasing consumer loyalty volatility due to more significant information accessibility and competitive choices. The study emphasizes that brands must adopt innovative, consumer-centric strategies to sustain trust and reliability. Implications: The findings stress the need for brands to integrate advanced technologies, ethical data practices, and sustainability into their marketing strategies. These insights offer practical guidance for navigating the digital marketplace, fostering long-term consumer loyalty, and aligning with evolving consumer expectations. Future research should explore these dynamics through empirical studies in diverse contexts.